Psychopathy and Decision-Making: Antisocial Factor Associated With Risky Decision-Making in Offenders - Yao, Xiaoqiang; Zhang, Fenghua; Yang, Tingting; Lin, Tao; Xiang, Ling; Xu, Fuming; He, Guanrui (Frontiers in Psychology, 2019)
Psychopathy is a personality development disorder increasing the risk of antisocial behavior. Studies on the relationship between psychopathy and decision-making have received limited attention and the result of studies is mixed. A present study examines whether or not the different factors of psychopathy are related to decision-making under risk and ambiguity in offenders and how they are related. Also, the study investigates whether general intelligence is associated with decision-making or moderates the relationship between psychopathy and decision-making. The results showed that only Antisocial factor of psychopathy significantly correlates with Game of Dice Task (GDT) risky selections, but there no general relation between psychopathy and Iowa Gambling Task (IGT) performance. Lastly, general intelligence neither is related to decision-making under risk and ambiguity nor moderates the relationship between decision-making and psychopathy. The study results show that Antisocial factor of psychopathy was associated with decision-making under risk rather than ambiguity. Our results also suggest that the Antisocial factor of psychopathy was more related to executive dysfunction in offenders.